Guitar Rig 2 power! - Orren Merton (Thomson Course Technology PTR, 2006)
But now that you have Guitar Rig 2, how do you maximize it to match your creative potential? Guitar Rig 2 Power! shows you the way. Far from a rehashing of the material in the manual, Guitar Rig 2 Power! explores the program's functions in a creative way that will not only help you get the most out of Guitar Rig, but will help you use it to make better sounds and become a better player. It begins with an overview of how to install and optimize Guitar Rig for your system, and from there advances to hands-on tutorials on creating your own rigs and using the various modules in the program. It wraps up by explaining how you can integrate Guitar Rig 2 into your own live and studio set-ups